Carbon Dioxide and Methane Fluxes from Various Vegetation Communities of a Natural Tropical Freshwater Wetland in Diferent Seasons - Were, David; Kansiime, Frank; Fetahi, Tadesse; Hein, Thomas (Environmental Processes, 2021)
Emission of carbon dioxide (CO2) and methane (CH4) is of interest in tropical wetland studies because the high and relatively stable temperatures year-round enhance both primary productivity and organic matter decomposition. Nonetheless, there is scarcity of data on emission of these carbon-based greenhouse gases from tropical wetlands. We investigated CO2 and CH4 fluxes from a natural tropical freshwater wetland in Uganda under different dominant vegetation communities, i.e., Cyperus papyrus (Papyrus), Typha latifolia (Typha) and Phragmites mauritianus (Phragmites), during the dry and wet seasons. Gas samples were collected using static chambers and analyzed by gas chromatography. Fluxes (mg C m−2 h−1) of both CO2 and CH4 from Papyrus (732.9 ± 48.7 [mean ± standard error] and 14.1 ± 0.8, respectively) and from Typha (759.7 ± 51.4 and 13.5 ± 1.2, respectively) insignificantly varied (p > 0.05) during the dry season. However, CO2 and CH4 fluxes from both vegetation communities during this season were significantly lower and higher (p < 0.05), respectively, than in Phragmites (871.8 ± 56.7 and 8.7 ± 0.5). During the wet season, no significant variation (p > 0.05) occurred among the three vegetation communities for both CO2 and CH4 fluxes (Phragmites: 691.9 ± 55.8 and 15.6 ± 1.1, Typha: 682.0 ± 53.3 and 16.3 ± 1.2, and Papyrus: 651.2 ± 49.0 and 17.1 ± 1.7, respectively). Water level was the main driver of CO2 and CH4 fluxes from the wetland, suggesting its importance in any efforts to regulate fluxes of both gases in tropical wetlands. We estimated total annual CO2 and CH4 emissions from Uganda’s wetland soils in the ranges of 159.5 × 106–180.2 × 106 t C (tonnes of carbon) and 278.9 × 104–359.7 × 104 t C, respectively.